2007
DOI: 10.1002/14651858.cd000270.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Community mental health teams (CMHTs) for people with severe mental illnesses and disordered personality

Abstract: Background Closure of asylums and institutions for the mentally ill, coupled with government policies focusing on reducing the number of hospital beds for people with severe mental illness in favour of providing care in a variety of non-hospital settings, underpins the rationale behind care in the community. A major thrust towards community care has been the development of community mental health teams (CMHT). Objectives To evaluate the effects of community mental health team (CMHT) treatment for anyone with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0
11

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 103 publications
(56 reference statements)
5
97
0
11
Order By: Relevance
“…1 It is particularly concerning that patients with schizophrenia spectrum disorders and bipolar disorders tend to have high rates of nonadherence and service disengagement varying between 23% and 30% even in specialized early psychosis programs. 2,3 Various diagnosis-nonspecific outpatient care models have been developed to treat patients with severe mental illness (eg, community mental health teams, 4 intensive case management, 5 and assertive community treatment). [6][7][8][9] Most previous assertive community treatment studies 10 have included patients with various psychiatric disorders.…”
mentioning
confidence: 99%
“…1 It is particularly concerning that patients with schizophrenia spectrum disorders and bipolar disorders tend to have high rates of nonadherence and service disengagement varying between 23% and 30% even in specialized early psychosis programs. 2,3 Various diagnosis-nonspecific outpatient care models have been developed to treat patients with severe mental illness (eg, community mental health teams, 4 intensive case management, 5 and assertive community treatment). [6][7][8][9] Most previous assertive community treatment studies 10 have included patients with various psychiatric disorders.…”
mentioning
confidence: 99%
“…Studies comparing satisfaction with different treatment models in psychiatric services have shown greater satisfaction with assistance provided by community mental health teams as compared to standard care (Malone et al, 2010). However, no studies have been found to focus on satisfaction with care received from different service providers by people with SMI living in a community.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, it appears that hospital admissions can be avoided provided there is a service that respects and responds to the specific needs of these individuals. 11 The following statements illustrate the accurate and contextualized perception of the teams regarding the suicide attempts, which underline the importance of interdisciplinary work, bringing health interventions closer to the experienced reality.…”
Section: The Network That Embraces the Client Who Attempted Or Is At mentioning
confidence: 96%
“…Therefore, a partnership must be established between the subject, their family and the professional, considering that this rehabilitation process also involves the local community. [7][8][9][10][11][12][13][14][15] To achieve this, the professionals reported an extremely important component, the construction or recovery of attachment, both with the client as well as with their relatives, in this specific time of psychological suffering, as can be observed in the following statements:…”
Section: ] When We Believe the Risk Is Very High We Request The Cmentioning
confidence: 99%
See 1 more Smart Citation